Case report: Systemic tuberculosis with prostate involvement mimicking prostate cancer with multiple metastases on 18F-FDG and 18F-PSMA PET/CT - Sun, Xinyao; Qiu, Yongkang; Song, Lele; Kang, Lei (Frontiers in Medicine, 2024)
Background: Prostate tuberculosis is a common form of male urogenital tuberculosis.Clinical and imaging manifestation of prostate tuberculosis are atypical, which often need to be differentiated from benign prostatic hyperplasia, prostate malignant tumor, and urinary tract infection. Although prostate specific membrane antigen (PSMA) is considered as a specific biomarker for prostate cancer, it is also found within tuberculosis tissues which may be stimulated by angiogenic factors. Abnormal PSMA uptake on positron emission tomography combined with computed tomography (PET/CT) should exclude the possibility of tuberculosis.Case Report: Here, we report a case of a 51-year-old man with elevated erythrocyte sedimentation rate (ESR) but normal PSA. 2-Deoxy-2-[fluorine-18]-fluoro-D-glucose ( 18 F-FDG) and [fluorine-18]-prostate specific membrane antigen ( 18 F-PSMA) PET/CT were used for further evaluation. The prostate showed high FDG uptake but with slight uptake of PSMA.Multiple osteolytic bone destruction, lymph nodes with increased FDG uptake but mild PSMA uptake were observed throughout the body. Based on the prostate biopsy and the positive result of tuberculous infection of T cell spot test, systemic tuberculosis was diagnosed.Following six months of standard anti-tuberculosis treatment, the patient experienced symptom relief.In the case of urinary tract infection where the prostate shows high FDG uptake lesions with perilesional abscess, mildly increased PSMA uptake, low PSA value, high ESR and relevant clinical symptoms, tuberculosis should be considered and laboratory tests are required, especially when symptoms are relieved after successful anti-tuberculosis therapy.The final confirmation of the diagnosis still relies on pathological examination.